Cowboy Singin’ - Kelly Werts (Symphony in the Flint Hills, 2010)
Tradition, origins, and developments of cowboy singing.
Keywords: cowboy; cows; cattle; longhorns; driving; drives; songs; books; lonely; night; watch; hymns; ballads; Chisholm Trail; composition; composing; singing; community; campfire; culture; fiddle; harmonica; guitar; pioneer; poetry